Bosnia and Herzegovina : Request for Extended Arrangement Under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for Bosnia and Herzegovina. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Bosnia and Herzegovina's request for an Extended Arrangement Under the Extended Fund Facility. Growth in Bosnia and Herzegovina was 3.2 percent in 2015, despite fiscal consolidation as a result of financing constraints, and is expected to be about the same in 2016. The authorities adopted a comprehensive reform agenda in early 2015 that aims to address tepid growth and high unemployment in a sustainable manner. Given the commitment by the authorities at all levels to steadfastly implement their program and to adjust policies as circumstances change, the IMF staff expects the economy of Bosnia and Herzegovina to progress in dealing with its present challenges. The IMF staff supports the authorities' request for an extended arrangement.